2016
DOI: 10.1515/jee-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Multi–Scale Synthesized View Assessment Based on Morphological Pyramids

Abstract: The Depth-Image-Based-Rendering (DIBR) algorithms used for 3D video applications introduce geometric distortions affecting the edge coherency in the synthesized images. In order to better deal with specific geometric distortions in the DIBR synthesized images, we propose full-reference metric based on multi-scale pyramid decompositions using morphological filters. The non-linear morphological filters used in multi-scale image decompositions maintain important geometric information such as edges across differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…We conducted comparison experiments between our proposed model and several FR, RR and NR metrics, including nine 2D-FR metrics [10][11][12][28][29][30][31][32], three 2D-NR metrics [15,33,34], one 3D-FR metric [35], two 3D-NR metrics [16,36], five Multi-views FR metrics [13,14,37,38], one Multi-views NR metric [39] and one LF-RR metric [18]. Three evaluation criteria are selected to measure the correlation between MOS and predicted results, consisting of Spearman Rank Order Correlation Coefficient (SROCC), Linear Correlation Coefficient (LCC) and Root Mean Squared Error (RMSE).…”
Section: B Comparison With Previous Objective Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted comparison experiments between our proposed model and several FR, RR and NR metrics, including nine 2D-FR metrics [10][11][12][28][29][30][31][32], three 2D-NR metrics [15,33,34], one 3D-FR metric [35], two 3D-NR metrics [16,36], five Multi-views FR metrics [13,14,37,38], one Multi-views NR metric [39] and one LF-RR metric [18]. Three evaluation criteria are selected to measure the correlation between MOS and predicted results, consisting of Spearman Rank Order Correlation Coefficient (SROCC), Linear Correlation Coefficient (LCC) and Root Mean Squared Error (RMSE).…”
Section: B Comparison With Previous Objective Metricsmentioning
confidence: 99%
“…MS-SSIM [11] and FSIM [12]. MP-PSNR Full [13] and MP-PSNR Reduc [14] based on Morphological pyramid decomposition are proposed to evaluate the multi-view image quality. RR methods only require part of information from original images.…”
Section: Introductionmentioning
confidence: 99%
“…Battisti et al [2] proposed more sophisticated framework for evaluating the quality of depth image based rendering techniques by comparing the statistical features of wavelet subbands and used image registration and skin detection steps for additional optimization. Sandic et al [30] exploited multi-scale pyramid decompositions with morphological filters for obtaining the quality of intermediate views and showed that they achieve significantly higher correlation with subjective scores. These methods form a class of metrics specific to view-interpolation artifacts, and 2D stimuli containing the interpolated views are used for subjective experiments.…”
Section: Previous Workmentioning
confidence: 99%
“…RMP-PSNR [7] and 3DSwIM [8]. Table 1 summarizes the experiment results, where the best results are marked in boldface.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…In [6], MW-PSNR was improved by using morphological pyramids, producing the Morphological Pyramid Peak Signalto-Noise Ratio (MP-PSNR) method. The reduced version of MP-PSNR (RMP-PSNR) [7] was also presented, which only used MSEs on higher scales. In [8], the blocks in reference and synthesized images were first registered.…”
Section: Introductionmentioning
confidence: 99%